Ion permeability of isolated chromaffin granules (The Rockefeller University Press, 1976)
The passive ion permeability, regulation of volume, and internal pH of isolated bovine chromaffin granules were studied by radiochemical, potentiometric, gravimetric, and spectrophotometric techniques. Chromaffin granules behave as perfect osmometers between 340 and 1,000 mosM in choline chloride, NaCl, and KCl as measured by changes in absorbance at 430 nm or from intragranular water measurements using 3H2O and [14C]polydextran. By suspending chromaffin granules in iso- osmotic media of various metal ions and selectively increasing the permeability to either the cation or the anion by intrinsically permeable ions or specific ionophores, it was possible to determine by turbidity and potentiometric measurements the permeability to the counterion. These measurements indicate that the chromaffin granule is impermeable to the cations tested (Na+, K+, and H+). Limited H+ permeability across the chromaffin granule membrane was also shown by means of the time course of pH re-equilibration after pulsed pH changes in the surrounding media. The measurement of [14C]methylamine distribution indicates that a significant deltapH exists across the membrane, inside acidic, which at an external value of 6.85 has a value of 1.16. The deltapH is relatively insensitive to changes in the composition of the external media and can be enhanced or collapsed by the addition of ionophores and uncouplers. Measurement at various values of external pH indicates an internal pH of 5.5. Use of the ionophore A23187 indicates that Ca++ and Mg++ can be accumulated against an apparent concentration gradient with calcium uptake exceeding 50 nmol/mg of protein at saturation. These measurements also show that Ca++ and Mg++ are impermeable. Measurement of catecholamine release under conditions where intravesicular calcium accumulation is maximal indicates that catecholamine release does not occur. The physiological significance of the high impermeability to ions and the existence of a large deltapH are discussed in terms of regulation of uptake, storage, and release of catecholamines in chromaffin granules.